Healing of skin wounds using a new cocoon scaffold loaded with platelet-rich or platelet-poor plasma. Issue 11 (19th January 2017) - Liu, Jiawei; Lu, Fei; Chen, HongLei; Bao, Rong; Li, Zhiquan; Lu, Bitao; Yu, Kun; Dai, Fangying; Wu, Dayang; Lan, Guangqian
Abstract : The cocoons of the silkworm Bombyx mori are widely used as biofunctional materials. Abstract : The cocoons of the silkworm Bombyx mori are widely used as biofunctional materials. In the present study, cocoon composites (CCs) were treated with a solution consisting of calcium chloride, ethanol, and distilled water, resulting in partial dissolution, followed by freeze-drying, yielding cocoon scaffolds (CCSs). The CCSs were then immersed in autologous platelet-rich plasma (PRP) or platelet-poor plasma (PPP) obtained from rabbits and freeze-dried again, allowing us to harvest the other two composite materials (CCSs + PRP and CCSs + PPP). Analysis of the physical and biological properties of the materials demonstrated that the water absorption and retention capacities of CCSs had improved. After loading with PRP or PPP, both of the composite materials significantly promoted the growth of L929 cells, with CCSs + PRP showing slightly better results. Additionally, in vivo studies showed that both of the composite materials could enhance the process of wound healing, with the CCSs + PRP exhibiting the best results. Thus, our results suggested that these composites may have potential applications in the biomedical field.